Speaking abouth the death - Manuel Márquez Garrido; José Arenas Fernández; Diego José Feria Lorenzo; Rocío León López; Ana Barquero González; María del Carmen Carrasco Acosta; Ana Carmen Macías Rodríguez (Universidad de Alicante, 2012)
The sense of the following article is to present a familiar reading for many professionals of cares and new for others, sometimes the intuition has taken us to improve the cares, appearing professional concepts as confidence, empathy, autonomy, cares and hope, that enable to us more and more for a therapeutic relation of quality. We valued, as very important, to know the psychological different phases through which passes the terminal patient.